Establishment of Distinct MyoD, E2A, and Twist DNA Binding Specificities by Different Basic Region-DNA Conformations - Kophengnavong, Thiphaphone (American Society for Microbiology, 2000)
Basic helix-loop-helix (bHLH) proteins perform a wide variety of biological functions. Most bHLH proteins recognize the consensus DNA sequence CAN NTG (the E-box consensus sequence is underlined) but acquire further functional specificity by preferring distinct internal and flanking bases. In addition, induction of myogenesis by MyoD-related bHLH proteins depends on myogenic basic region (BR) and BR-HLH junction residues that are not essential for binding to a muscle-specific site, implying that their BRs may be involved in other critical interactions. We have investigated whether the myogenic residues influence DNA sequence recognition and how MyoD, Twist, and their E2A partner proteins prefer distinct CAN NTG sites. In MyoD, the myogenic BR residues establish specificity for particular CAN NTG sites indirectly, by influencing the conformation through which the BR helix binds DNA. An analysis of DNA binding by BR and junction mutants suggests that an appropriate BR-DNA conformation is necessary but not sufficient for myogenesis, supporting the model that additional interactions with this region are important. The sequence specificities of E2A and Twist proteins require the corresponding BR residues. In addition, mechanisms that position the BR allow E2A to prefer distinct half-sites as a heterodimer with MyoD or Twist, indicating that the E2A BR can be directed toward different targets by dimerization with different partners. Our findings indicate that E2A and its partner bHLH proteins bind to CAN NTG sites by adopting particular preferred BR-DNA conformations, from which they derive differences in sequence recognition that can be important for functional specificity.